Student conceptual level scale: Development and initial validation - Yang, Xi; Dong, Jia; Tan, DingLiang (Frontiers in Education, 2022)
The conceptual level is an index of personality development. In the field of teaching, the conceptual level is seen as a dynamic learning style. It has important implications for student learning and individual growth, as well as guidance for teaching. However, the lack of a measurement tool with a clear internal structure for the conceptual level of students has slowed the development of the theory and made it difficult to implement the teaching. To address these issues, this study describes the initial development and validation of the Student Conceptual Level Scale (SCLS) with four samples of students (n = 1,321) drawn from eight secondary schools in China.. We constructed a second-order three-factor model of the SCLS consisting of three factors—learning awareness level, autonomous input level, and environmental coping level—each with its own independent set of items. This study validated the use of full-scale and subscale scores and examined their relationship with different validity criteria: autonomous learning, mental effort, and academic scores. This updated measure reflects the value and role of the conceptual level in the learning and individual development of students and also provides a more complete frame of reference for the use of the conceptual level in teaching and learning.